Looking at...Brachiosaurus : a dinosaur from the jurassic period. - Amery, Heather (Milwaukee : Gareth Stevens Pub, 1993)
Describes the physical characteristics and probable behavior of this herbivorous dinosaur with spiked thumbs.
Keywords: Brachiosaurus -- Juvenile literature; Dinosaurs